FUTURE MIGRATION DECISIONS: AN EXPERIMENTAL APPROACH - Apsite-Berina, Elina; Krisjane, Zaiga; Burgmanis, Girts (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The volatile political and institutional scene in Europe implies that future migration-related decision making can be re-assessed. Implications that migrants face might lead to a remarkable shift in migration trajectories and the need to adopt various future geographic mobility decisions. Therefore, this paper demonstrates to what extent the experimental approach can illustrate future migration-related decision making. This study explores the geographic selectivity of migration intensions of international students under four hypothetical scenarios. The data was collected in 2019 from a sample of international students in Latvia, accounting for 500 experimental participants.The findings suggest that majority of international students studying in Latvia would prefer relocation. Besides, it is indicative that institutional barriers such as the need for a visa are much less critical than economic conditions, wage level and overall quality of life. Such indicative factors as wage level increase in Latvia would substantially boost the possibility to stay in Latvia; however, changes related to family or personal reasons are essential triggers for the students to return to their home countries.